Safety of pediatric HIV elimination: the growing population of HIV- and antiretroviral-exposed but uninfected infants. - Lynne M Mofenson; D Heather Watts (PLoS Medicine)
Lynne Mofenson and Heather Watts discuss the context and implications of the study by J. Sibuide and colleagues, which provides a detailed analysis of birth defects in infants with in utero antiretroviral drug exposure in the French Perinatal Cohort. Please see later in the article for the Editors' Summary.